Functional electrical stimulation in adult patients with cerebral palsy and foot drop-outcome in gait - Gather, Katharina Susanne; Bleichner, Niklas; Block, Julia; Heitzmann, Daniel; Weichold, Claudia; Wolf, Sebastian Immanuel; Alimusaj, Merkur; Putz, Cornelia (Prosthetics and orthotics international, 2025)
Background:  - Foot drop is a common condition for patients with upper motor neuron syndrome such as cerebral palsy (CP). This study aimed to investigate the effects of functional electrical stimulation (FES) on gait function, quality of life, and FES satisfaction in adults with CP and foot drop. To analyze effects over time, an observational, longitudinal study was performed. - Methods:  - In this observational prospective cohort study, 8 adults with CP (median age of 22 years; range: 18.5-33.25) received a FES system for 12 weeks. 3D gait analysis was performed at beginning (T1) and end of the study period (T2). To detect effects of FES, ankle kinematics, kinetics, and spatiotemporal parameters were monitored for the conditions FES-OFF and -ON at each examination. - Results:  - Over time, walking speed increased significantly from T1ON (1.08 m/s) to T2OFF (1.21 m/s) with further improvement at T2ON. The ON-OFF difference of maximum dorsiflexion during swing tended to increase at T2 (2.49 degrees) compared with T1 (1.73 degrees) but with a more plantarflexed ankle position at T2 (range: −7.1 to 1.31 degrees) than T1 (range: −1.53 to 4.51 degrees) resulting in a significant decrease between T1ON and T2OFF. With FES, push-off energy tended to decrease for both examinations and lead to lower values over time. - Conclusion:  - Positive therapeutic effects are represented in walking speed over time regardless of FES being OFF or ON even with a reduction in push-off energy. Despite no significant increase in maximum dorsiflexion in swing, over time, participants showed the tendency of an improvement in foot lift with FES-ON.
Gesehen am 23.02.2026